Agribusiness Prospects of Kachai Lemon Produced in Ukhrul District of Manipur, India: Status, Issues and Way Forward - Heikham Narmila Devi; Gino A Sangma (Archives of Current Research International, 2024)
Kachai lemon (Citrus jambhiri Lush.) is a variety of citrus, known for its rich nutritional and medicinal benefits due to its high flavonoid content and ascorbic acid. It has played a significant role in enhancing the socio-economic development of the tribal communities by generating income and employment opportunities. The Geographical Indication (GI) tag awarded to Kachai lemon has increased its commercial cultivation and market value. This recognition and growing attention have led to the emergence of agripreneurs and farmer producer organizations (FPOs) for production, value addition and marketing of Kachai lemon in an organized manner. The present study is aimed to compile the success stories, challenges of farmers and explore various Kachai lemon brands available on online platforms. A SWOT (Strength, Weakness, Opportunities and Threats) analysis on production and marketing of kachai lemon was performed. For the study, descriptive analysis was carried out to assess its potential, current status and challenges. The study suggests that in order to compete globally, it is crucial to develop strong post-harvest processing and marketing systems with support from agencies and institutions to provide valuable resources and market linkages to enhance efficiency and gain economic benefits.